Actualizing Leadership Development of College Teachers (Journal of Educational Sciences, 2025)
At the present stage, teacher leadership, pedagogical leadership as a concept that uses the potential of pedagogical experience and influential leadership, is an urgent topic. The study of the conditions and mechanisms of the formation and development of teacher leaders,their abilities to change the environment,inspirepositive things is an area of advanced research in ТVE.Тhe purpose of the article: to study the need for leadership formation(non-positional leadership) among college teachers in the context of a radical modernization of the TVE system and to find answers to the questions:what elements of leadership are relevant to the TVE system and what are the demands of college teachers in developing their leadership skills and abilities?The scientific significance lies in substantiating the understanding of the leadership of TVE teachers,updating its developmentin the context of new challenges facing TVE according to the Development Concept, and announcing the Year of Professions. The practical significance lies in the fact that the empirical experience of understanding the need for leadership development by college teachers is summarized through questionnaires,quantitative and qualitative eanalysis of the data obtained, and the development of recommendations for designing content for the development of teachers' leadership skills.The research methodology was based on the positions of the Concept of distributed Leadership and Hoyle's idea of enhanced professionalism. To confirm the research hypothesis, a set of methods was used: analysis, comparison, questionnaires, mathematical processing of data, interpretation and generalization of data .  200teachers from Shymkent and Almaty colleges participated in the survey.The obtained results allowed us to conclude that college teachers well and clearly understand the importance of pedagogical leadershipin ensuring qualitative changes in TVE, and they know their needs and goals in leadership development.In general, they rate the leadership of their supervisors and colleagues well.However,some difficulties hindered the development of teachers' leadership.This is an incorrectorganization of the professional work of the staff(workload,constant monitoring, stress), an authoritarian leadership pstyle, lack of specialized knowledge, and personal limitations.In this regard, the authors propose the content of practice-oriented classes separately for college administrators and teachers, taking into account the uniqueness of their professional activities.Keywords: leadership, leadership pqualities, pedagogical upgrade, transformation, agent, change.